Multi Area Multi Objective Dynamic Economic Dispatch with Renewable Energy and Multi Terminal DC Tie Lines - Musau, Moses Peter; Abungu, Nicodemus Odero; Wekesa, Cyrus Wabuge (My University, 2016)
In this paper, an improved wheeling method (IWM) for a fully constrained five –area multi area multi objective dynamic economic dispatch (MAMODED) with renewable energy(RE) is proposed where the area interconnections is achieved using multi terminal DC(MTDC) tie lines for the first time. A three-method hybrid of Modified Firefly Algorithm with Levy Flights and Derived Mutation (MFA-LF-DM) is used to illustrate the optimization of the system. The levy flights reduce the random movement of the objective function while the derived mutations are improve the exploration of the candidate solution. The uncertainties and variability of the renewable sources are modelled using scenario based method (SBM). A comparison will be made using the MAMODED with RE but traditional HVAC interconnections. The simulation results reveal that integration of RE led to an IWM with reduced cost and emissions.Further use of MTDC interconnection gave better optimal results as compared to the traditional HVAC tie lines.
Keywords: HVAC; Modified Firefly Algorithm with Levy Flights and Derived Mutation (MFA-LF-DM); MTDC, Multi Area Multi Objective Dynamic Economic Dispatch (MAMODED)